SELBIR SETTLEMENT (GABALA DISTRICT) - Toxfa Talış qızı T.Huseynova (Theoretical Hypotheses and Empirical Results, 2025)
The article is informed about the ancient city of Caucasian Albania. Gabala Selbir area speaking about the presence of residence the author said that at the end of the B.C II millennium and the first half I millennium the ancient city had become the grown main place. The article notes based on big scientific principles as a result of archeological excavation obtained findings informed that the ancient city belong to IV century